Developing Land in Florida with Fire in Mind: Recommendations for Designers, Developers, and Decision-Makers - Martha Monroe; Raelene Crandall; Jennifer Fill; Susan Marynowski (EDIS)
Fire protection is a necessary consideration when building homes and designing neighborhoods in Florida. The type, amount, and structure of vegetation surrounding the development and individual houses will affect the risk that homes will catch fire. Architects and developers can significantly reduce wildfire risk for those living and working in Florida by using fire-resistant materials and managing the landscape around developments. This publication details specific recommendations for planning and designing defensible developments, including wildfire mitigation planning, vegetation management, and home construction, and how to balance the risks with the costs of risk mitigation strategies.